Rare Coinfection of Scrub Typhus and Malaria in Immunocompetent Person - Ashok Sharma (Online Journal of Health & Allied Sciences, 2012)
Scrub Typhus, or tsutsugamushi disease is a febrile illness caused by bacteria of the family Rickettsiaceae and named Orientia tsutsugamushi. Recently it has been found to endemic in Subhimalayan region of India.Malaria is highly endemic in rest of India but its prevalence is low in Subhimalayan region because of the altitude. We report a rare case of a patient having coinfection with scrub typhus and malaria.